Pemberdayaan Keluarga Dalam Pencegahan Stunting Di Nagari Pariangan Kabupaten Tanah Datar - Rahmadani Yusran; Deprianto Deprianto; Abdul Hakim; Vikry Alvi Putra; Zaky Wirananta (Pusat Riset dan Inovasi Nasional, 2023)
Stunting is a problem that is specifically faced by the world, this is indicated by the increasing occurrence of disturbances in the development and functioning of a child's mental and monitoring conditions. The problem of stunting should not be ignored by the government,because the problem of stunting will greatly impact children's vulnerability to facing life, children who are considered stunted will be more easily exposed to disease and experience severe mental difficulties. The implementation method used is the qualitative research method, the underlying thing is because the implementation of community service activities takes direct data on the field and the Jorong Padang Panjang auxiliary health center. As well as taking additional information from books, journals and the internet so that the fulfillment of information regarding stunting and balanced nutrition is more complete. The implementation of this empowerment is expected that later the community will be able to understand and understand stunting and be able to apply it in life. The focus of this stunting activity is not only on toddlers and children but also aimed at women who are of childbearing age, as well as family members within the scope of the house and fulfillment of nutrition must be prepared early on even before pregnancy.